Theoretical and Methodological Approach of Diagnostics of Innovation and Investment Potential of the Enterprise - Полозова, Т. В.; Кисліченко, А. П.; Рабеах Мохаммед (ХНУРЕ, 2021)
The competitiveness of enterprises is largely determined by the efficiency of their innovation and investment potential, which is an important component of effective enterprise development. Therefore, in modern business conditions, the relevance of development and implementation of theoretical and methodological approaches to the diagnostics of innovation and investment potential of enterprises is increasing.
DOI: 10.30837/978-966-659-336-1
Keywords: innovation; investment; investment; innovation and investment potential; economic diagnostic; diagnostics of innovation and investment potential of the enterprise